English Teacher Education In Malaysian Tertiary Institutions: Aligning Tqm To The Determinants Of Quality - Issa, Jinan Hatem (2013)
Quality is the leading goal that organisation’s management strives for accomplishing in its everyday performances. English teacher education programs should be, like any other educational programs, featured with quality. The quality of English teacher education is critical and a focus of the English Teaching profession. Hence, this study seeks to develop the understanding regarding this particular area of ELT in Malaysian tertiary institutions. This study demonstrates evidences and suggests guidelines on the importance of delivering quality English teacher education programs through exploring whether the embedding of Total Quality Management core principles may lead to produce quality English teacher education via measuring the indicators of four forms of capital (intellectual, financial, spiritual, and social) as determinants of quality. An exploratory case study was carried out using a purposive sampling technique. Sixty-nine heads and lecturers of English teacher education programs, at five major public Malaysian tertiary institutions, completed two questionnaires on the determinants of quality and the effective implementation of TQM. The finding sustained a focus on improving the quality of English teacher education programs through selecting high quality staff being capable of and devoted to addressing the visions and missions of quality English language teacher education programs. Besides, excelling in research, publications and community work should feature the quality programs. The findings indicated the highest and lowest indicators of each of the four forms of capital. Moreover, the top priorities of the determinants of quality were identified.